15x+(x+2)=10+6x+(-x+3)

Simple and best practice solution for 15x+(x+2)=10+6x+(-x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 15x+(x+2)=10+6x+(-x+3) equation:


Simplifying
15x + (x + 2) = 10 + 6x + (-1x + 3)

Reorder the terms:
15x + (2 + x) = 10 + 6x + (-1x + 3)

Remove parenthesis around (2 + x)
15x + 2 + x = 10 + 6x + (-1x + 3)

Reorder the terms:
2 + 15x + x = 10 + 6x + (-1x + 3)

Combine like terms: 15x + x = 16x
2 + 16x = 10 + 6x + (-1x + 3)

Reorder the terms:
2 + 16x = 10 + 6x + (3 + -1x)

Remove parenthesis around (3 + -1x)
2 + 16x = 10 + 6x + 3 + -1x

Reorder the terms:
2 + 16x = 10 + 3 + 6x + -1x

Combine like terms: 10 + 3 = 13
2 + 16x = 13 + 6x + -1x

Combine like terms: 6x + -1x = 5x
2 + 16x = 13 + 5x

Solving
2 + 16x = 13 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
2 + 16x + -5x = 13 + 5x + -5x

Combine like terms: 16x + -5x = 11x
2 + 11x = 13 + 5x + -5x

Combine like terms: 5x + -5x = 0
2 + 11x = 13 + 0
2 + 11x = 13

Add '-2' to each side of the equation.
2 + -2 + 11x = 13 + -2

Combine like terms: 2 + -2 = 0
0 + 11x = 13 + -2
11x = 13 + -2

Combine like terms: 13 + -2 = 11
11x = 11

Divide each side by '11'.
x = 1

Simplifying
x = 1

See similar equations:

| X/p+x/q=a | | 1/2(2t+3)=2/3(6t-1) | | 16=7x | | 3/2x+1=5-2x | | 3=2c-4 | | -16=-4/3X | | 3e-1=15.8 | | 3p=25.8 | | 2x+8=3x+14 | | 2*1/5/4/5 | | 0/47x10x3 | | 3w^2-13w=10 | | 21/5/4/5 | | 6(a+1)=36 | | f/5+5=-7 | | 2x-5+7x=-32 | | m/6-5/8=7/8 | | 4e-8=16 | | -(5y+1)-(4y-6)=3 | | x/2+x/9=5+2 | | (x-y)(x-y)=0 | | 5n^2+12=-19n | | 4x-(5x+2)=4x-27 | | -7x^2-64x-1=0 | | 2x+8-7x+1=3x-1+2x-5 | | 2/3X+1/4Y-5=0 | | 3a-2a+7=3+5 | | 15-3x=6+x-4x | | 10y+-10=22 | | 6x-10y=24findy | | A+B+B+B+B+80+90=100 | | 3(2x-1)-4(x+2)=5(2x+3)-7(x-2) |

Equations solver categories